Functional reaction times of a simulated blocking test among para taekwondo athletes - O`Sullivan, D. M.; Jeong, H. S.; Won, H. J. (healthcare, 2022)
Para taekwondo is a combat sport martial art that requires fast reaction times for successful defense during fighting. The current classification system is based on the function and the effective length of the upper limbs, which affects the athlete`s ability to block. Therefore, this study aimed to investigate the differences between the different classes in the athlete`s ability to block and move around the ring. A total of 87 Para taekwondo (K42, K43, and K44) athletes` data were analyzed. Each participant engaged in the blocking reaction time test in a fighting stance with the left leg in front, the right leg in front, and the legs parallel in random order. A foot-stepping reaction test was performed to anlyze how the athletes moved in various directions. The results indicated no significant differences between the classes for the lower body foot stepping reaction times and the upper body blocking performance times. The stimulated blocking time of the Para taekwondo athletes ranged from 0.79 to 0.97 s Furthermore, the neurological group (0.86 ± 0.09 s) was significantly slower than the amputation/dysmelia group (0.81 ± 0.07 s). We thus concluded that the neurologically impaired athletes were disadvantaged and therefore belonged in a separate class.